We are wearing out the naughty step - Inkpen, Mick (Hodder Children's Books, 2008)
We are wearing out the Naughty Step - I lost the school hamster, and Josh fed the elephant the wrong way and we made the dog into a panda...Mummy is not happy...but the day she makes Kevin a chocolate birthday cake is the day that ALL of us, including Mummy, end up on the Naughty Step!